Nicolás Sáez de Elola, intrépido capitán en la Conquista del Perú. El oro de Cajamarca - Miguel Lesaca, Miren (Boletín de la Real Sociedad Bascongada de Amigos del País, 2012)
Nicolás Sáez de Elola, captain of Pizarro and one of the winners with Inca treasure, returned to his native Azpeitia ﬁlled with a wealth are not comparable to any other seen before. His biography and works are the story of all those adventurers who sought their fortune in overseas and whose lives were developed in parallel with those big names that have been linked to the modern history.